Role of the Sympathetic Nervous System and Its Modulation in Renal Hypertension - Sata, Yusuke; Head, Geoffrey A.; Denton, Kate; May, Clive N.; Schlaich, Markus P. (Frontiers in Medicine, 2018)
The kidneys are densely innervated with renal efferent and afferent nerves to communicate with the central nervous system. Innervation of major structural components of the kidneys, such as blood vessels, tubules, the pelvis, and glomeruli, forms a bidirectional neural network to relay sensory and sympathetic signals to and from the brain. Renal efferent nerves regulate renal blood flow, glomerular filtration rate, tubular reabsorption of sodium and water, as well as release of renin and prostaglandins, all of which contribute to cardiovascular and renal regulation. Renal afferent nerves complete the feedback loop via central autonomic nuclei where the signals are integrated and modulate central sympathetic outflow; thus both types of nerves form integral parts of the self-regulated renorenal reflex loop. Renal sympathetic nerve activity (RSNA) is commonly increased in pathophysiological conditions such as hypertension and chronic- and end-stage renal disease. Increased RSNA raises blood pressure and can contribute to the deterioration of renal function. Attempts have been made to eliminate or interfere with this important link between the brain and the kidneys as a neuromodulatory treatment for these conditions. Catheter-based renal sympathetic denervation has been successfully applied in patients with resistant hypertension and was associated with significant falls in blood pressure and renal protection in most studies performed. The focus of this review is the neural contribution to the control of renal and cardiovascular hemodynamics and renal function in the setting of hypertension and chronic kidney disease, as well as the specific roles of renal efferent and afferent nerves in this scenario and their utility as a therapeutic target.